Borehole climatology. - Bodri, Louise; ScienceDirect eBooks (Amsterdam : Elsevier, 2007)
Climate for the 21st century is expected to be considerably different from the present and recent past. Industrialization growth combined with the increasing CO2 concentration in the atmosphere and massive deforestation are well above the values over the past several decades and are expected to further grow. Air temperature is rising rapidly well as does the weather variability producing frequent extreme events. Six of the ten warmest years occurred in the 1990s. Temperatures predicted for the 21st century ranges well above the present day value. The time period of the last 100-200 years covered by the direct meteorological observations is too short and does not provide material to reliably assess what may happen over the next hundred(s) years. A faithful prediction of the future requires understanding how climate system works, i.e. to reconstruct past climate much further in the past. Borehole paleoclimatology enables climate reconstruction of the past several millennia, unlike proxy methods provides direct past temperature assessment and can well broaden the areal range to the remote regions poorly covered with meteorological observations. Considerable debates have recently focused on the causes of the present-day warming, i.e. to distinguish between the natural and anthropogenic contribution to the observed temperature increase, eventually to quantify their regional distribution. Complex interpretation of borehole data with the proxies and additional socio-economic information can hopefully help. On observed data taken in various places all over the world we demonstrate suitable examples of the interaction between the subsurface temperature response to time changes in vegetation cover, land-use (farming) and urbanization. Precise temperature-time monitoring in shallow subsurface can further provide the magnitude of the present-day warming within relatively short time intervals. As far as we know, there exists so far no book dealing entirely with the subject of the Borehole climatology. Only relatively rarely this method is mentioned in otherwise plentiful literature on climate reconstruction or on climate modelling. There are, however, series of papers focussing on various borehole--climate related studies in numerous journals (e.g. Global and Planetary Change, Climate Change, Tectonophysics, Journal of Geophysical Research, Geophysical Research Letters, etc). Time to time a special issue appears to summarize papers on this topic presented during specialized symposia. Key Features - Description of a new useful alternative paleoclimate reconstruction method - A suitable source of information for those wishing to learn more about climate change - Material for lecturing and use in the classroom - Ample practical examples of borehole temperature inversions worldwide - Ample illustrations and reference list - Authors have a good knowledge of the problem based on more than 20 years of experience, one of them actually pioneered the method Key Features - Description of a new useful alternative paleoclimate reconstruction method - A suitable source of information for those wishing to learn more about climate change - Material for lecturing and use in the classroom - Ample practical examples of borehole temperature inversions worldwide - Ample illustrations and reference list - Authors have a good knowledge of the problem based on more than 20 years of experience, one of them actually pioneered the method.
Preface -- Chapter I. Background and History of the Problem -- Chapter II. Climate Change and Subsurface Temperature -- Chapter III. Ground Temperature Histories: evidence of changing climate -- Chapter IV. Subsurface Temperature Monitoring: present-day temperature change and its variability.
Print version record.
Elsevier
Keywords: Paleoclimatology -- Holocene; Paleoclimatology -- Methodology; Holocene Geologic Period; Paleoclimatology; Paleoclimatology -- Methodology; From 10 thousand years ago; Electronic books